The effect of green investment, profitability, and company size on financial sustainability: A study on the IDX 30 Index for the period 2016-2023 - Andi Wijanarko; Andini Nurwulandari; Hasanudin Hasanudin; Irma Setyawati (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2025)
This study aims to investigate the partial influence of Green Investment, Profitability, and Company Size on Financial Sustainability against the background of the importance of sustainability in all sectors, including industry. This study uses a quantitative method. The study examines 14 stable companies listed on the IDX 30 from 2016 to 2023, selected through purposive sampling. It utilizes secondary data collected via the study-desk method. Data analysis is conducted using multiple linear regression with SPSS 23. According to the study's findings, financial sustainability is somewhat positive but is slightly influenced by green investments, profitability, and company size. The causes of the three hypotheses only have a positive effect, but not significant, because there are variables that are more dominant in influencing Financial Sustainability, the time spectrum has a significant effect only in the long term, a significant influence only occurs after combining the mediator or moderator variables, the relatively small sample size, industry differences, and research site variations.